2015
DOI: 10.1039/c4ra12425a
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot synthesis of 4-substituted semicarbazides

Abstract: A diverse library of twenty-five 4-mono-and disubstituted semicarbazides was prepared in a one-pot twostep approach. The method includes formation of a carbamate from bis(2,2,2-trifluoroethyl)carbonate or 2,2,2-trifluoroethylchloroformate and a primary or secondary amine and subsequent interaction of the carbamate with hydrazine to result in a semicarbazide. The approach allowed to obtain 4-substituted semicarbazides on a large scale in good yield and high purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This new reactivity also provided a new route to semi-carbazides that could serve as building blocks for more complex derivatives. 16 …”
Section: Resultsmentioning
confidence: 99%
“…This new reactivity also provided a new route to semi-carbazides that could serve as building blocks for more complex derivatives. 16 …”
Section: Resultsmentioning
confidence: 99%
“…This aspect makes aryl carbonates an attractive eco-friendly alternative for the synthesis of O -aryl carbamates, especially with aromatic amines. 16 A literature search also revealed that N -alkyl O -aryl carbamates have been synthesized from the reaction of aliphatic amines with chloroformates. 21 As many drugs such as cefoxitine, linezolide, darunavir, brecanavir, irinotecan, ritonavir, and URB524 contain aliphatic N -side chains, the N -alkyl O -aryl carbamates are required for the synthesis of these molecules.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…Isocyanates, in turn, are synthesized using phosgene and its surrogates such as diphosgene and triphosgene; other frequently used methods to generate isocyanates involve Curtius rearrangement, 14 Hoffmann rearrangement, 15 and Lossen rearrangement. 16 In this study, urea derivatives are synthesized from the reaction of amines with carbamates via isocyanates, which are generated from the carbamates in situ. Carbamates were synthesized by carbamoylation reaction of carbonates with amines.…”
mentioning
confidence: 99%
“…In this context, 2,2,2-trifluoroethyl chlorooxoacetate ( 1b ) (Scheme ) could be a more reactive alternative to 1a (the p K a values of 2,2,2-trifluoroethanol and ethanol are 12.5 and 16, respectively) , which would enable the one-pot strategy under the parallel synthesis conditions. Our previous experience with the 2,2,2-trifluoroethyl derivatives, bis­(2,2,2-trifluoroethyl) carbonate and 2,2,2-trifluoroethyl chloroformate, revealed that moderate reactivity of these reagents compared with the ethyl and the phenyl or the p -nitrophenyl analogs supported efficient stepwise aminolysis in the one-pot syntheses of unsymmetrical ureas and 4-substituted semicarbazides. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Our previous experience with the 2,2,2-trifluoroethyl derivatives, bis(2,2,2-trifluoroethyl) carbonate and 2,2,2-trifluoroethyl chloroformate, revealed that moderate reactivity of these reagents compared with the ethyl and the phenyl or the pnitrophenyl analogs supported efficient stepwise aminolysis in the one-pot syntheses of unsymmetrical ureas and 4-substituted semicarbazides. 6,35,36 To confirm our hypothesis and to evaluate the one-pot strategy in the parallel synthesis of N 1 -aryl-N 2 -alkyl-substituted oxamides, we performed the experiments with reagents 1a and 1b utilizing various amines. The current report describes our results on the method evaluation and presents the comparative study of the efficacy of the above ester chlorides under the parallel synthesis conditions.…”
Section: ■ Introductionmentioning
confidence: 99%